The Design of the Outer-Rotor Brushless DC Motor and an Investigation of Motor Axial-Length-to-Pole-Pitch Ratio - OYMAN SERTELLER, NECİBE FÜSUN (My University, 2022)
In this study, the effects of the ratio of a motor\"s axial length to its pole pitch on efficiency, magnetic flux density distribution, torque, torque/weight, and motor volume were investigated in an outer-rotor (hub) brushless direct current motor. The weight and volume of an electrical machine affects the output power, efficiency and output torque, and it is advantageous to design an electric motor at an appropriate power and high efficiency with an appropriate weight and volume. Therefore, the aim of this study was to optimize the motor\"s axial length and stator outer diameter, which affects the motor volume. Initially, the axial-length-to-pole-pitch ratio of the hub BLDC motor was taken at 0.75. According to this ratio, the dimensions of the rotor outer diameter, rotor inner diameter, stator outer diameter, stator inner diameter, slot height, motor axial length, and magnet thickness were optimally determined. Then, the axial-length-to-pole-pitch ratio was considered as 1, 1.50, 2, and 3, respectively. The effects of the change in the motor\"s axial-length-to-pole-pitch ratio on the efficiency, torque, speed, torque/volume, torque/weight, and cogging torque were examined in a simulation environment. According to the motor\"s axial-length-to-pole-pitch ratio, the torque value in the final state was 28.65% higher than the torque value in the initial state. In the last part, the motor axial length and the stator outer diameter were defined as variables in a genetic algorithm procedure and optimized. The number of poles and the number of slots were fixed parameters. Simulation studies were carried out using the finite element method via AN-SYS/Maxwell software.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Tarımsal Bilimler; Çevre Mühendisliği; Mühendislik ve Teknoloji; Social Sciences and Humanities; Sociology; Agricultural Sciences; Environmental Engineering; Engineering and Technology; YEŞİL VE SÜRDÜRÜLEBİLİR BİLİM VE TEKNOLOJİ; Çevre / Ekoloji; Tarım ve Çevre Bilimleri (AGE); ÇEVRE BİLİMLERİ; ÇEVRE ÇALIŞMALARI; Sosyal Bilimler Genel; Sosyal Bilimler (SOC); GREEN & SUSTAINABLE SCIENCE & TECHNOLOGY; ENVIRONMENT/ECOLOGY; Agriculture & Environment Sciences (AGE); ENVIRONMENTAL SCIENCES; ENVIRONMENTAL STUDIES; SOCIAL SCIENCES, GENERAL; Social Sciences (SOC); Genel Sosyal Bilimler; Doğa ve Peyzaj Koruma; Yönetim, İzleme, Politika ve Hukuk; Çevre Bilimi (çeşitli); Su Bilimi; Fizik Bilimleri; Sosyal Bilimler ve Beşeri Bilimler; Yaşam Bilimleri; General Social Sciences; Nature and Landscape Conservation; Management, Monitoring, Policy and Law; Environmental Science (miscellaneous); Aquatic Science; Physical Sciences; Social Sciences & Humanities; Life Sciences; hub BLDC design; efficiency; axial length to pole pitch ratio; optimization; genetic algorithm; PERMANENT-MAGNET; OPTIMIZATION; MACHINE; hub BLDC design; efficiency; axial length to pole pitch ratio; optimization; genetic algorithm